Multilateral counter-terrorism the global politics of cooperation and contestation - Romaniuk, Peter (Routledge global institutions, 2010)
This text explains the history of counter-terrorist co-operation, examining under what conditions states cooperate to suppress terrorism as well as how existing international institutions have been affected by the US-led 'global war on terror,' launched after the 9/11 terrorist attacks